A comparative framing analysis of the coverage of Syrian and Ukrainian refugees by the Finnish National Broadcast Company Yle - Lehtolainen,Inka-Maria (2023)
Abstract Over the past decade, refugee movements have had an increasing impact on Europe and the topic has dominated both political and news media discourse. During this time, portrayals of refugees have varied from victims to threats. The media, as an institution of control and communication, has the power of shaping the public’s views and discussions regarding the refugees. It also has the ability to normalize certain portrayals while alienating others and holds influence over the public’s understanding of measures taken by the government concerning refugees. Hence, the purpose of this thesis is to compare and contrast the framing of two respective refugee ‘crises’ by the Finnish Broadcasting company Yle. This study focuses on the September 2015 arrival of Syrian refugees and the March 2022 arrival of Ukrainian refugees in Finland. This thesis is grounded in the idea that media has a significant role in the construction of reality, attitudes, and knowledge towards refugees and the reasons behind them fleeing. By excluding certain information and including others in the frameworks being used, a specific message is sent to the audience. Therefore, framing becomes an important factor in creating the narrative of the situation’s reality. This thesis undertakes an inductive, comparative qualitative content analysis, utilizing both framing theory and grounded theory. Further, this study seeks to enhance the understanding of the representation of two differing refugee groups, and how the refugee ‘crises’ are framed. The analysis of the thesis contributes to the understanding of the differences in Yle’s frames of the refugees and the ‘crises’ and what it reveals about the broader socio-political context.
Keywords: Key words: Syrian refugees; Ukrainian refugees; framing; media portrayal; comparative study